Komunikasi Orang Tua dan Tingkat Stres Mahasiswa Perantauan Pada Larangan Mudik Covid 19 - Ahmad Khairul Nuzuli Ahmad Khairul Nuzuli (KOMUNIDA : Media Komunikasi dan Dakwah, 2020)
This research is motivated by a ban on going home which is treated by the government as a result of the Pandemic Covid-19. This study aims to see whether there is an influence between the intensity of communication with parents on the level of stres in overseas students who cannot go home. The paradigm of this research is positive, with explanatory type. The theoretical foundation in this study is the Reference Group Theory. The theory used to explain the effect of communication intensity with parents (Independent Variable) in reducing stress levels in overseas students of Amikom University Yogyakarta after the Covid-19 pandemic homecoming ban (dependent variable) is the theory of the Hyman referral group. The sample in this study were 50 overseas students of Amikom University in Yogyakarta who did not go home to their hometown. The results showed a significant influence between the variables of communication intensity with parents (X) on stres levels in overseas students of Amikom University Yogyakarta (Y)